Popularity - Gabriella Conti; Andrea Galeotti; Gerrit Mueller; Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2009)
What makes you popular among your high-school peers? And what are the labor market returns to popularity? We investigate these questions using an objective measure of popularity derived from sociometric theory: the number of friendship nom- inations received from schoolmates. We provide novel evidence that early family en- vironment, school composition and school size play a signicant role in determining popularity. We show that the estimated wage return to one additional nomination is about 2 percent the popularity premium. This amounts to roughly 40 percent of the return to one more year of education. A revised version of this paper is published in the Fall 2013 issue of the Journal of Human Resources.
Keywords: 330